European Climate Law – real changes or postponed future? - Amorim, Carlos de Abreu (2021)
One cannot question the scientific evidence of the deterioration of the planet’s environmental quality and the global climate emergency. The apparent growth of denialism in the climate debate does not bring anything positive. The European Green Deal (“EGD”) appeared as a consolidated strategy to fight climate change, but the world is not the same as it was in December 2019. Even before the COVID-19 crisis, there were doubts about the viability of such a powerful political and financial investment. As we try to deal with the fallout of the COVID-19 pandemic and guide our economies to recovery, risks of diversion or misuse of these environmental funds seemed possible. Fortunately, environmental common sense seems to have prevailed. In an unforeseen but potentially happy marriage, the Recovery Plan for Europe and the EGD were united in their purposes and in their concrete action. The European Climate Law (“ECL”) is the first binding legal instrument born of the EGD. With a non-mishap-free preparation process, the final version provokes contradictory feelings. First, the perception that one could have gone further is inescapable. On the other hand, what is already acquired is relevant and Europe is unlikely to go back on this essential matter. There are innovations in the ECL that significantly altered the Commission’s original proposal, introducing new elements. But while some of these changes appear to have been forced by the new circumstances, others may be proof that Member States do not have the same predisposition to deal with the objectives of the EGD and the fight against climate change. The safest way to contradict this inclination is to strengthen the ECL as a key tool in the implementation of the European Union’s environmental and policy strategy.